Quality control of [177Lu]Lu-PSMA preparations using HPLC: effect of sample composition and ligand on recovery - Else A. Aalbersberg; Tammie T. Cao; Martine M. Geluk-Jonker; Jeroen J. M. A. Hendrikx (SpringerOpen, 2022)
Abstract Background [177Lu]Lu-PSMA is used for the treatment of metastatic castration-resistant prostate cancer. For in-house productions, quality control methods are essential for ensuring product quality, and thus patient safety. During HPLC method development for quality control of [177Lu]Lu-PSMA-I&T, we noticed an unpredictable variability in peak area and height with replicate measurements. After a run, irremovable radioactivity was measured over the whole the length of the HPLC column, with slightly higher activity at the beginning and end of the column. The uniform distribution suggests that [177Lu]Lu-PSMA-I&T interacts with the column. As a result of the interaction, incomplete and variable recovery of injected activity was observed leading to the variability in peak area and height. Therefore the aim of this study was to (1) investigate the effect of sample composition on the interaction of [177Lu]Lu-PSMA-I&T to the HPLC column (measured as recovery, peak area, and peak height), and (2) to compare this with same concentrations of the well-known [177Lu]Lu-PSMA-617. Results Sample composition significantly affects recovery of [177Lu]Lu-PSMA-I&T, leading to a change in peak area and height. Recovery was 24% when diluted with 0.1 mM octreotide, 38% with water, and increased to 95% when diluted with 0.7 mM unlabeled PSMA-I&T. Peak area and height decreased to 26% and 17% when diluted in octreotide and to 41% and 29% when diluted in water, compared to a dilution in PSMA-I&T. Further experiments showed that recovery (and consequently peak area and peak height) reached a plateau of > 99% at concentrations of 0.27 mM and higher. [177Lu]Lu-PSMA-617 also interacts with the HPLC column, leading to lower, but less variable, recovery (9%). The low recovery of [177Lu]Lu-PSMA-617 could not be prevented with addition of unlabeled PSMA-617. Conclusion [177Lu]Lu-PSMA-I&T can undergo an irreversible binding with an HPLC column resulting in a decreased recovery. The recovery is can be highly dependent on sample composition. The addition of a surplus of unlabeled PSMA-I&T leads to an accurate analysis of [177Lu]Lu-PSMA-I&T.